Chemical Constituents, Pharmacologic Properties, and Clinical Applications of Bletilla striata - Xu, Delin; Pan, Yinchi; Chen, Jishuang (Frontiers in Pharmacology, 2019)
Bletilla striata, a traditional Chinese medicinal plant of the genus Bletilla belong to Orchidaceae family, is known to help for the elimination of disease risk factors, prevent chronic diseases and promote health status. In this review article, there is an extensive literature reviewed on the chemical constituents, pharmacological properties and clinical application of B. striata. However, the mechanisms of action of its active ingredients are not yet clear. So, its chemical composition and pharmacological effects are remains to explored further in this review. Linking the knowledge of traditional Chinese medicinal plants with modern pharmacology is provided a way to systematically study the activity of medicinal plants and serve as the basis for clinical research. This paper also examined the traditional Chinese medicine of B. striata from a more scientific perspective by summarizing its chemical components, their pharmacological activities and clinical research to provide a scientific basis for medical research, new drug development and clinical application.